STRENGTHENING MSME RESILIENCE IN THE TOURISM SECTOR: A QUALITATIVE STUDY OF POST-PANDEMIC MARKETING STRATEGIES IN INDONESIAN NON-STAR HOTELS - Marhendra, Audio Valentino Himawan; Fauzan, Daffa Abrar Nur (Jurnal Education and Development, 2026)
COVID-19 pandemic severely impacted the global hotel industry, profoundly jeopardizing the operational viability and long-term existence of Micro, Small, and Medium Enterprises (MSMEs). Achieving Sustainable Development Goal (SDG) 8, which focuses on promoting Decent Work and Economic Growth, necessitates the protection and reinforcement of these small firms to guarantee the enduring and comprehensive revival of the tourism sector. This study meticulously examines the strategic alterations in marketing methods employed by Fellas Inn Family Guest House, a non-star hotel MSME situated in Malang, Indonesia, as a dynamic response to the unprecedented challenges posed by the post-pandemic landscape. We utilized a rigorous qualitative case study approach to gather in-depth empirical data through comprehensive semi-structured interviews with management and operational staff, complemented by extensive digital observation. The core findings indicate a critical and necessary strategic pivot: the corporation fully discontinued its traditional reliance on price-based marketing in favor of adopting "trust-based marketing," which successfully leveraged enhanced safety and rigorous cleanliness standards as the primary, non-negotiable selling points. Furthermore, the analysis reveals that the primary factor contributing to the successful resurgence of occupancy rates was the sophisticated integration of digital ecosystems, notably the synergistic connection between social media content and Online Travel Agents (OTAs). This research significantly enhances the theoretical comprehension of crisis management within the hospitality sector by demonstrably illustrating how strategic digital transformation and agile adaptation bolster the resilience of MSMEs. The results provide a crucial, replicable model demonstrating how proprietors of non-prestigious hotels can effectively sustain profitable operations and secure market stability in an ever-evolving market environment.